Analysis of Constraints against Efficiency of Seaport-hinterland Logistics in Nigeria - Adepoju, Olusegun Onifade (Periodica Polytechnica Transportation Engineering, 2024)
Having realized that most Nigerian seaports are congested and the problem of moving goods have been difficult, the Federal Government through Bureau of Public Enterprises and Nigerian Shippers’ Council were mandated to identify Inland Container Depots (ICDs) and Container Freight Stations (CFSs) across the country with connectivity to rail transport. Since 2004 to date, these have mostly not been functioning. This paper therefore examined the constraints and possible factors responsible. The Nigerian Ports Authority, Road Haulage Association, Terminal Operators, selected Shipping companies were used as respondents. 34.1% (253) from the population of 743 respondents were sampled with the use of Cochran formula and stratified random sampling technique. Shaphiro Test and multiple regression were used to analyze the constraints against the use of ICDs and CFSs. Principal Component Analysis was used to extract the major factors hindering port-hinterland logistics in Nigeria. It was observed that 50% of general logistics constraints emanated from lack of efficient rail system, enforcement and finance combined. Extracted causative factors against port-hinterland movements of goods are: inadequate terminal capacity, parking and inadequacy of cargo handling facilities. The research concluded that both general constraints and causative factors are to be looked into with stringent policy enforcement.